Association of mate tea (Ilex paraguariensis) intake and dietary intervention and effects on oxidative stress biomarkers of dyslipidemic subjects - Boaventura, Brunna Cristina Bremer; Di Pietro, Patrícia Faria; Stefanuto, Aliny; Klein, Graziela Alessandra; de Morais, Elayne Cristina; de Andrade, Fernanda; Wazlawik, Elisabeth; da Silva, Edson Luiz (Nutrition (Burbank, Los Angeles County, Calif.), 2012)
To evaluate the effect of long-term ingestion of mate tea, with or without dietary intervention, on the markers of oxidative stress in dyslipidemic individuals. Seventy-four dyslipidemic volunteers participated in this randomized clinical trial. Subjects were divided into three treatment groups: mate tea (MT), dietary intervention (DI), and mate tea with dietary intervention (MD). Biochemical and dietary variables were assessed at the beginning of the study (baseline) and after 20, 40, 60, and 90 d of treatment. Participants in the MT and MD groups consumed 1 L/d of mate tea. Those in the DI and MD groups were instructed to increase their intake of fruit, legumes and vegetables and decrease their consumption of foods rich in cholesterol and saturated and trans-fatty acids. Biomarkers of oxidative stress such as antioxidant capacity of serum (ferric reducing antioxidant potential assay), uric acid, reduced glutathione, paraoxonase-1 enzyme, lipid hydroperoxide (LOOH), and protein carbonyl were analyzed. Participants in the DI group showed a significant decrease in total fat and saturated fatty acid intakes. Those in the DI and MD groups presented a significant increase in vitamin C consumption. For all groups, there was a significant increase in ferric reducing antioxidant potential and reduced glutathione concentrations but no significant changes in LOOH, protein carbonyl, and paraoxonase-1 values. The reduced glutathione concentration was positively correlated with the consumption of monounsaturated fatty acids, fiber, and vitamin C, whereas levels of LOOH were inversely correlated with intakes of vitamin C and fiber. In addition, LOOH correlated positively with low-density lipoprotein cholesterol and inversely with high-density lipoprotein cholesterol, which had a positive association with paraoxonase-1. The ingestion of mate tea independently of the dietary intervention increased plasma and blood antioxidant protection in patients with dyslipidemia.